The Effect of Problem Based Learning Model Assisted with Poster Media on Students’ Critical Thinking Skills - Lutfiahtulzanah; Mayarni (Universitas Pendidikan Ganesha, 2024)
The lack of analytical proficiency among elementary school students is evident from their insufficient training in answering contextual questions that require analysis. Consequently, their ability to critically evaluate their work is quite limited. This study aims to examine the impact of the PBL model using poster media on students' understanding of expressing opinions in elementary science and social studies (IPAS) lessons. This research employs a quantitative experimental methodology using a nonequivalent control group design. The population consists of 60 students divided into an experimental group and a control group. Rational analysis shows that the N-Gain percentage in the experimental group is superior to that in the control group, with the experimental group achieving an N-Gain percentage of 72.44%, compared to 38.61% in the control group. The results of the paired sample t-test found that the sig. (2- tailed) value was 0.000 < 0.05. The research indicates that the use of PBL assisted by poster media provides significant feedback on students' critical thinking skills. From this data, it can be stated that there is an impact of PBL assisted by poster media on students' ability to observe critically in fifth-grade IPAS lessons.